Two or Three Things about Desire - Cruz, Conchitina (Xianggang guo ji shi ge zhi ye 2013., 2014)
Drawn from International Poetry Nights in Hong Kong 2013, Two or Three Things About Desire is a chapbook of poetry by Conchitina Cruz presented in English, and Chinese. Two or Three Things About Desire is also available, along with the chapbooks of other internationally renowned poets, in Islands or Continents (Eighteen-volume Set). Selected poems from this volume are featured in the anthology Islands or Continents: International Poetry Nights in Hong Kong 2013.